NZ J Ecol 2016
DOI: 10.20417/nzjecol.40.12
|View full text |Cite
|
Sign up to set email alerts
|

Snares crested penguins Eudyptes robustus population estimates 2000–2013

Abstract: New Zealand (NZ) is an internationally significant area for penguins. All NZ penguin species are listed in 'at risk' threat categories. The naturally uncommon Snares crested penguins (Eudyptes robustus), which are restricted to NZ subantarctic islands, are highly susceptible to localised stochastic events and human activities. There has been uncertainty about population size and trends for Snares crested penguins. We surveyed the nest abundance and distribution of Snares crested penguins on Northeast (NE) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, this may not always be the case because a number of penguin species show large population changes over short temporal scales, and these events are not reflected in any longterm trends, indicating that birds are alive but not at colonies every year (e.g. northern rockhopper penguin, Cuthbert et al 2009;southern rockhopper penguin, Crawford et al 2008;Baylis et al 2013b; Snares crested penguin, Hiscock & Chilvers 2016;macaroni penguin, Trathan et al 2012; gentoo penguin Pygoscelis papua, Baylis et al 2013a). The Fiordland crested penguin may also not attempt to breed every year because many monitoring sites showing considerable variation between years in the number of nests detected.…”
Section: Population Trajectorymentioning
confidence: 99%
“…However, this may not always be the case because a number of penguin species show large population changes over short temporal scales, and these events are not reflected in any longterm trends, indicating that birds are alive but not at colonies every year (e.g. northern rockhopper penguin, Cuthbert et al 2009;southern rockhopper penguin, Crawford et al 2008;Baylis et al 2013b; Snares crested penguin, Hiscock & Chilvers 2016;macaroni penguin, Trathan et al 2012; gentoo penguin Pygoscelis papua, Baylis et al 2013a). The Fiordland crested penguin may also not attempt to breed every year because many monitoring sites showing considerable variation between years in the number of nests detected.…”
Section: Population Trajectorymentioning
confidence: 99%
“…Surveys of E. sclateri suggest that populations were stable until 2011, but have subsequently declined by 19% (Hiscock and Chilvers, 2014). In contrast, Warham (1974), Mattern (2013) and Hiscock and Chilvers, (2016) suggested that E. robustus populations have remained stable. By contrast, the extent to which any such demographic shifts might have impacted the genetic composition of Eudyptes populations remains unclear.…”
Section: Introductionmentioning
confidence: 98%